THE EFFECT OF ATTITUDE ON ENTREPRENEURIAL INTENTION AMONG STUDENTS IN SOUTH TANGERANG - Samjuannita, Angel Veronica; Puspitowati, Ida (Graduate Program of Universitas Tarumanagara, 2023)
This research was conducted to empirically test the effect of need for achievement, need for autonomy, creativity, and risk taking on entrepreneurial intentions among students in South Tangerang. Respondents in the study amounted to 233 people who were students from three universities in Southern Tangerang. This study uses a non-probability sampling technique with purposive sampling in obtaining primary data to be processed using Smart Partial Least Square (SmartPLS) software. This study discovered that the need for achievement and creativity have a positive and significant effect on entrepreneurial intentions, while the need for autonomy and risk taking have a positive but not significant effect on entrepreneurial intentions.